X-sqrt(X+3)=3

Simple and best practice solution for X-sqrt(X+3)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-sqrt(X+3)=3 equation:


Simplifying
X + -1sqrt(X + 3) = 3

Reorder the terms:
X + -1qrst(3 + X) = 3
X + (3 * -1qrst + X * -1qrst) = 3
X + (-3qrst + -1qrstX) = 3

Solving
X + -3qrst + -1qrstX = 3

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '3qrst' to each side of the equation.
X + -3qrst + 3qrst + -1qrstX = 3 + 3qrst

Combine like terms: -3qrst + 3qrst = 0
X + 0 + -1qrstX = 3 + 3qrst
X + -1qrstX = 3 + 3qrst

Reorder the terms:
-3 + X + -3qrst + -1qrstX = 3 + 3qrst + -3 + -3qrst

Reorder the terms:
-3 + X + -3qrst + -1qrstX = 3 + -3 + 3qrst + -3qrst

Combine like terms: 3 + -3 = 0
-3 + X + -3qrst + -1qrstX = 0 + 3qrst + -3qrst
-3 + X + -3qrst + -1qrstX = 3qrst + -3qrst

Combine like terms: 3qrst + -3qrst = 0
-3 + X + -3qrst + -1qrstX = 0

The solution to this equation could not be determined.

See similar equations:

| 21x+x^3+7.88=0 | | 5y+2322=2852 | | 2x-1.3=-12.7 | | -15*12= | | 3-2x-x^2= | | 2x^2-22x+30=5 | | 4t+8=9t+6 | | 9x^2-48x-192=0 | | 9*1.333-2*4.118= | | 1.3333+4*4.117= | | -22=-2T-4 | | 25+4y-5=12y-10-2y | | 34y=140 | | 1.3333+4*3.66666=16 | | 3y-7+y+23=6y+20-4y | | 1.333+4y=16 | | 28-13x-6x^2= | | (-3+3)(x+8)= | | 3x+8-2x=12 | | 5x-29=-25+6x | | 12-4(x+2)=3x-11 | | 5s-8=-36+s | | a^2-2a+1= | | a^2-2a+11= | | -9(-3x+10)= | | 5(2x-7)=-5(-39-4x) | | 13x=32*5x | | W^2+14w+24=0 | | 2x+16+4=12 | | 16a^2-56ab+49ab^2= | | 4z^2-8z-5=0 | | x-6x-845=0 |

Equations solver categories